Sumber - Sumber dan Kontribusinya dalam Pendapatan Rumah Tangga Tani di Lahan Pasang Surut Kecamatan Barambai Kabupaten Brito Kuala Kalimantan Selatan - Erlinda Yurisinthae; Sri Widodo; Slamet Hartono; Irham Irham (Jurnal Dinamika Sosial Ekonomi, 2004)
The cultivation of tidal swamp for agriculture had been done since a long time ago with traditional system and have potential to be develop in the future. But many constraints those cause low income for agriculture household. To solve this problem, agriculture household make diversification on farm or look for another job away from farm (off farm activity). The samples are devided in two groups, agriculture household that have overflow land (181 samples) and no overflow land (119 samples). The results from the research show, the off farm activity have great contribution to total income for agriculture household. The efforts of diversification by using home yard and take care of livestock had not yet gave high contribution yet.Key word: Income Source, Income Contribution, Tidal Swamp